The Application of PFMEA for Roller Bearings Production - Krejci, Lucie; Schindlerova, Vladimira; Bucko, Michal; Hlavaty, Ivo; Mician, Milos (Manufacturing Technology Journal, 2019)
An important trend today is the continual improvement of product quality with the objective of increased customer satisfaction, but also leading to more effective cost reduction management. Effective quality management in a company also enables increasing production productivity thanks to the increasing amount of top-quality products made and the consequent minimalization of repairs of non-conforming workpieces. This contribution deals with one of the important tools for ensuring quality in the production process using the FMEA (Failure Mode and Effect Analysis) method used in the production of roller bearings for the automobile industry.
Keywords: PFMEA; The analyses of defects and their consequences; Bearings; Automobile industry; Quality